The Impacts of Unfolded Protein Response in the Retinal Cells During Diabetes: Possible Implications on Diabetic Retinopathy Development - Alam, Kaiser; Akhter, Yusuf (Frontiers in Cellular Neuroscience, 2021)
Diabetic retinopathy (DR) is a vision threatening, chronic and challenging eye disease in the diabetic population. Despite recent advancement in the clinical management of diabetes, DR remains the major cause of blindness in working age adults. Better understanding the molecular and cellular basis of DR development will aid in identifying therapeutic targets. Emerging pieces of evidence from recent research in the field of ER stress have demonstrated a close association between unfolded protein response (UPR) associated cellular activities and DR development. In this minireview we shall provide an emerging understating of how UPR influences DR pathogenesis at cellular level.